President's Message - Khotar, Rupinder; Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2015)
OUTGOING PRESIDENT’S MESSAGE OK so this is my last last message (blush). I have shared many thoughts with you over the past two years and I hope that you, at some point in time, connected with my messages. You and I are interrelated. Our work connects us and gives us a common purpose. I hope that during your career you take the opportunity to be a positive influence on another. Volunteer at work, in your community, or on an international project. Make the most of your potential to provide education, encouragement and support. I hope that you endeavour to achieve more and to succeed at everything you do. INCOMING PRESIDENT’S MESSAGE his is my first message as the new ORNAC President. As a Perioperative Registered Nurse I have spent most of my 27 year career as a front line perioperative nurse and RN First Assistant. I am from Antigonish, NS, and have been involved with my professional associations, both provincially through ORNANS and nationally through ORNAC, and with many perioperative committees and working groups. This background gives me a strong understanding of the issues facing our membership and profession.